The Effect of Different Formulations of Praziquantel in Reducing Worms in the Prepatent Period of Schistosomiasis in Murine Models - Paulino, Érica Tex; Ribeiro de Lima, Monique; Viçosa, Alessandra Lifsitch; Silva, Cleber Hooper da; Salomon, Claudio Javier; Real, Daniel Andrés; Leonardi, Dario; Mello Silva, Clélia Christina; Moraes Neto, Antonio Henrique Almeida de (Frontiers in Public Health, 2022)
Schistosomiasis is a widely distributed parasitic disease and one of the most important neglected tropical diseases globally, for which Praziquantel® (PZQ) is the only available treatment. In this context, tests with new PZQ formulations become relevant for disease control. This study evaluated the effects of PZQ treatment in the prepatent phase of schistosomiasis using two formulations: nanoencapsulated (PZQ-NANO) and active pharmaceutical ingredient (PZQ-API). Five experimental groups were established, for which the following serological parameters were evaluated: ALT, AST, ALP, and TP. Animals treated with PZQ-API at 15 and 30 days post-infection showed decreased eggs per gram of feces (EPG) compared to untreated infected animals. The same animals showed reductions of 63.6% and 65.1%, respectively, at 60 days post-infection. Animals treated with PZQ-NANO experienced no significant changes in EPG at any time of observation. Animals treated with either PZQ-API or PZQ-NANO had higher ALT and AST levels in the patent period (60 and 90 days post-infection). Treatment with PZQ, either API or NANO, at 15 days post-infection reduced AST, ALT, and TP levels. It is concluded that prepatent treatment with PZQ-API can reduce the parasite load of infected animals and that treatment at 15 days post-infection can prevent increased serum levels of ALT, AST, and TP.